Design Guideline for Bangkok Neighborhood Park Furniture Supporting Good Life Quality and Creative activities for urban living: A Case Study of Areesamphan Park - Supsoontornkul, Nopmanee (Journal of Architectural/Planning Research and Studies (JARS), 2021)
The research article presents the study results and the design guideline for Bangkok neighborhood park furniture in the pre-design phase. Furniture designers and public park officers can apply the guideline for creating park furniture suitable for users and locations. The study area was Areesamphan park at the government public relations department. There were 2 phases of the research method. The first phase was to study existing Areesamphan park, furniture uses, users’ needs,and case study. Data was collected by observation and 150 questionnaires with interview. The second phase was the pre-design thinking process to develop the design guideline for solving existing furniture’s problems and creating new furniture concepts. There are 3 important conclusions. First, existing furniture should be improved and neccessary park furniture should be provided for solving functional problems. Second, the new park furniture design should focus mainly on functions, green design or harmony with nature, and design identity respectively. Third, the design for Bangkok neighborhood park furniture should consider functional problems, users’ needs, and equitable uses.